2020
DOI: 10.7554/elife.55130
|View full text |Cite
|
Sign up to set email alerts
|

VIP interneurons in mouse primary visual cortex selectively enhance responses to weak but specific stimuli

Abstract: Vasoactive intestinal peptide-expressing (VIP) interneurons in the cortex regulate feedback inhibition of pyramidal neurons through suppression of somatostatin-expressing (SST) interneurons and, reciprocally, SST neurons inhibit VIP neurons. Although VIP neuron activity in the primary visual cortex (V1) of mouse is highly correlated with locomotion, the relevance of locomotion-related VIP neuron activity to visual coding is not known. Here we show that VIP neurons in mouse V1 respond strongly to low contrast f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
93
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(108 citation statements)
references
References 42 publications
12
93
3
Order By: Relevance
“…These neurons are also highly integrated with motor circuits, where they can reciprocally regulate activity levels 52,68 . Our study and previous ones show that upregulating VIP interneuron excitability can locally enhance sensory evoked layer 2/3 population responses in somatosensory, visual and auditory cortex [26][27][28] , as well as the tuning of specific sensory features . Conversely, interfering with VIP neuron activity impairs visual response selectivity, learning and ocular dominance plasticity 29,30 .…”
Section: A Subset Of Vip Neurons Are Highly Sensitive To the Effects supporting
confidence: 80%
See 2 more Smart Citations
“…These neurons are also highly integrated with motor circuits, where they can reciprocally regulate activity levels 52,68 . Our study and previous ones show that upregulating VIP interneuron excitability can locally enhance sensory evoked layer 2/3 population responses in somatosensory, visual and auditory cortex [26][27][28] , as well as the tuning of specific sensory features . Conversely, interfering with VIP neuron activity impairs visual response selectivity, learning and ocular dominance plasticity 29,30 .…”
Section: A Subset Of Vip Neurons Are Highly Sensitive To the Effects supporting
confidence: 80%
“…In the present study, we reasoned that chemogenetic manipulation of cortical excitability through VIP interneurons, could provide a focal boost in periinfarct excitability in relatively non-invasive manner. VIP neurons play a powerful role in enhancing sensory responses in pyramidal neurons in visual and auditory cortex through disinhibition [26][27][28]52,53 . Consistent with previous findings, we found that increasing VIP interneuron excitability with chemogenetic stimulation could enhance forepaw evoked responses in somatosensory cortex for at least hour after CNO injection.…”
Section: Chemogenetic Stimulation Of Dis-inhibitory Vip Interneurons mentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithm parameters were tuned to reject potential ROIs with a peak spatial SNR below 2.5, a temporal SNR below 5, or a spatial corruption index above 1.5. Fluorescence traces for both somatic and dendritic ROIs were then extracted, neuropil-subtracted, demixed, and converted to Δ F/F traces, as described in [de Vries et al, 2020; Millman et al, 2020]. Together, neuropil subtraction and the use of a 180-second (5401 sample) sliding window to calculate rolling baseline fluorescence levels F for the Δ F/F computation ensured that the Δ F/F traces obtained were robust to potential differences in background fluorescence between mice and imaging planes.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that this visuomotor mismatch is driven by the comparison of excitatory, motor inputs with inhibitory, visual flow inputs 12,13 . However, neurons in V1 have a wide range of visual speed (or temporal frequency) preferences [14][15][16] , and running both drives V1 activity and modulates responses to visual stimuli 10,[17][18][19][20][21][22] . An alternate and untested hypothesis is that responses to sudden stops of visual flow are simply due to the convergence of motor and visual inputs, and do not arise from the precise coupling between an animals' actions and the visual stimulus.…”
Section: Introductionmentioning
confidence: 99%